2021
DOI: 10.3390/cancers13040833
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Genomic Vulnerabilities in the Post-Translational Ubiquitination, SUMOylation and Neddylation Machinery in Breast Cancer

Abstract: The dysregulation of post-translational modifications (PTM) transversally impacts cancer hallmarks and constitutes an appealing vulnerability for drug development. In breast cancer there is growing preclinical evidence of the role of ubiquitin and ubiquitin-like SUMO and Nedd8 peptide conjugation to the proteome in tumorigenesis and drug resistance, particularly through their interplay with estrogen receptor signaling and DNA repair. Herein we explored genomic alterations in these processes using RNA-seq and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In addition, therapeutic agents targeting UBE2C would synergise the effect of other therapies including chemotherapy, anti-oestrogen medications and radiation. Previous studies showed that overexpression of UBE2C reduces the therapeutic potency of letrozole, tamoxifen, doxorubicin and leads to radio-resistance in various BC cell lines [ 37 , 38 , 43 ]. These findings highlight the importance of further investigating the therapeutic and predictive potential of UBE2C expression in BC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, therapeutic agents targeting UBE2C would synergise the effect of other therapies including chemotherapy, anti-oestrogen medications and radiation. Previous studies showed that overexpression of UBE2C reduces the therapeutic potency of letrozole, tamoxifen, doxorubicin and leads to radio-resistance in various BC cell lines [ 37 , 38 , 43 ]. These findings highlight the importance of further investigating the therapeutic and predictive potential of UBE2C expression in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Various genes, including UBE2T, were found to be associated with an unfavourable prognosis in each BrC subtype (54). High expression of UBE2T indicated a lower pathological complete remission rate in patients with TNBC after neoadjuvant chemotherapy, and in patients with luminal BrC with tumor recurrence within 5 years after endocrine therapy or chemotherapy (96). Compared with that in the normal breast epithelial cell line MCF-10A, the expression of UBE2T was upregulated in BrC cells.…”
Section: Expression Of Ube2t In Cancermentioning
confidence: 99%
“…The relationship between gene expression levels and patient clinical prognosis in terms of relapse-free survival (RFS) and overall survival (OS) was evaluated using the Kaplan-Meier Plotter platform, as described previously [28,29] (accessed on 6 June 2020). This tool used gene expression and survival data from 7830 breast tumors (sources include GEO, EGA and TCGA).…”
Section: Outcome Analysismentioning
confidence: 99%